Randomized, Double-Blind, Dose-Finding Study for Tiotropium when Added to Olodaterol, Administered via the Respimat® Inhaler in Patients with Chronic Obstructive Pulmonary Disease. Issue 9 (September 2015) - Aalbers, René; Maleki-Yazdi, M.; Hamilton, Alan; Waitere-Wijker, Stella; Zhao, Yihua; Amatto, Valeria; Schmidt, Olaf; Bjermer, Leif
Abstract Introduction Combining long-acting muscarinic antagonists (LAMAs) and long-acting β2 -agonists (LABAs) is beneficial in chronic obstructive pulmonary disease (COPD), as the two classes of bronchodilator have complementary modes of action. The optimal dose for the fixed-dose combination of the LAMA tiotropium and the LABA olodaterol needed to be determined. In this phase II trial, the dose response of tiotropium on top of olodaterol was investigated in a free-dose combination, while other phase II studies have explored different doses of olodaterol on top of tiotropium, with both drugs delivered using the Respimat® inhaler. Methods This was a double-blind incomplete crossover trial in which 233 patients with moderate or severe COPD were randomized to receive four out of eight free-dose combinations of olodaterol (5 or 10 µg) and tiotropium (1.25, 2.5, or 5 µg) or placebo for 4 weeks each. Primary end point was trough forced expiratory volume in 1 s (FEV1 ) change from baseline (response) after 4 weeks. Results Addition of tiotropium 1.25, 2.5, and 5 µg to olodaterol 5 µg increased mean trough FEV1 response by 0.054, 0.065, and 0.084 L, respectively; addition of tiotropium 1.25, 2.5, and 5 µg to olodaterol 10 µg increased mean trough FEV1 response by 0.051, 0.083, and 0.080 L, respectively. All treatments were well tolerated and incidence of adverse events was similar with all treatments. Conclusions Overall, a dose response for tiotropium on top of both doses of olodaterol was observed, with increasing improvements in trough FEV1 compared to olodaterol alone as the tiotropium dose was increased. Funding Boehringer Ingelheim. Trial registration: ClinicalTrials.gov number, NCT01040403.